Mothering without a compass : white mother's love, Black son's courage - Thompson, Becky W. (University of Minnesota Press, 2000)
"In 1997, Becky Thompson began parenting nine-year-old Adrian at the request of his mother, changing both of their lives forever. Mothering without a Compass is the story of Thompson's first year as the white lesbian "sudden-mother" of an African American boy. From the everyday yet sometimes overwhelming tasks of finding Adrian a school and debating the significance of action figures, to unexpected discussions about who pays whom at the sperm bank and the more complicated matters of racism, sexuality, nontraditional families, open adoption, love, and loss, Thompson gives us an absorbing and often humorous account of her experience with antiracist, multicultural parenting." "Mothering without a Compass relates a lesbian parent's struggle to help her child grow up and describes the complexities facing children who have more than one family."--Jacket.